Re‐evaluation of karaya gum (E 416) as a food additive. (19th December 2016) - ,; Mortensen, Alicja; Aguilar, Fernando; Crebelli, Riccardo; Di Domenico, Alessandro; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Lambré, Claude; Leblanc, Jean‐Charles; Lindtner, Oliver; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Food Additives and Nutrient sources added to Food (ANS) was asked to deliver a scientific opinion on the re‐evaluation of karaya gum (E 416) as a food additive. Karaya gum (E 416) is an authorised food additive in the EU. Karaya gum (E 416) as specified in the Commission Regulation (EU) No 231/2012 is derived from the exudates from the stems and branches of strains of Sterculia urens Roxburgh and other species of Sterculia (family Sterculiaceae) or from Cochlospermum gossypium A.P. De Candolle or other species of Cochlospermum (family Bixaceae). An acceptable daily intake (ADI) 'not specified' was allocated by the Joint Food and Agriculture Organization/World Health Organization Expert Committee on Food Additives (JECFA), whereas the Scientific Committee for Food (SCF) allocated an ADI of 12.5 mg/kg body weight (bw) per day. Karaya gum is practically undigested and not degraded by intestinal microflora and it is most probably not or only negligibly absorbed unchanged in humans. There is no concern with respect to the genotoxicity of karaya gum from Sterculia spp. Karaya gum (E 416) from Sterculia spp. did not induce toxic effects in animals at dose levels up to 1, 250 mg/kg bw per day, the highest dose tested. Karaya gum from Sterculia spp. was well tolerated in humans at dose about 100 mg/kg bw per day for 4 weeks. The Panel concluded that there is no safety concern at the refined exposure assessment for the use of karaya gum as a food additive and that there is no need for a numerical ADI for karaya gum. The Panel further concluded that exposure to karaya gum by the use of this food additive should not exceed 7, 000 mg/person per day in adults, the level at which some experienced abdominal discomfort.